How the emergence of the omicron variant may change people’s attitudes toward the COVID-19 pandemic - Yang, Yong (Frontiers in Psychology, 2022)
Background. To examine people’s attitudes towards the COVID-19 pandemic before and after the emergence of the Omicron variant. Methods. Data were collected between November 15 and December 14, 2021, and the three attitudes included the negative influence on daily life, concerns of infection risk, and prediction of the ending of the pandemic. Results. The majority of people perceived daily life were at least somewhat negatively influenced by the COVID-19 pandemic, and worried at least once a week about infection risk. After the emergence of the Omicron variant, the perceived negative influence and concern of infection risk decreased slightly while the prediction of ending increased significantly. People who were infected by COVID-19 perceived more negative influence, more concern of infection risk, but more optimistic for the ending of the pandemic. People who did not get a vaccine perceived less negative influence, less concern of infection risk, but more pessimistic for the ending of the pandemic. The attitudes varied significantly by individual and contextual characteristics. Conclusions. The emergence of Omicron significantly increased people’s predicted ending time of the pandemic but did not change people’s perception of the pandemic’s negative influence on daily life and concern of infection risk